An Intelligent Decision Making System for Prospective Recipients of Cash Transfer (Bantuan Langsung Tunai) Using Simple Additive Weighting (SAW) Method - Yuntriani Yuntriani; Elvia Fajarwati; Ferry Susanto (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2023)
Bantuan Langsung Tunai (BLT) or cash transfer is the government's commitment to help underprivileged communities and to improve the economy along with improving the quality of life of underprivileged families. With BLT, it can help people to meet their daily needs. The responsibility of the government, especially in rural areas, is a problem which must be faced by the village administration, especially the village head. The village head has a responsibility towards the people in the village, and the village head is a government official at the village level who is tasked with distributing BLT. BLT funds are sourced from the Village Fund which has been distributed by the central government to help village communities affected by an unstable economy. This research was conducted with the aim of determining prospective recipients of BLT using the Simple Additive Weighting (SAW) method. The Simple Additive Weighting method is used because this method connects attribute values, where the value must be raised to the power of the attribute's weight value. In determining the recipient of BLT, there are many criteria which must be owned by the Community as a condition for obtaining BLT. The criteria used are the size of the house, floors, walls, toilet facilities, house electricity, water sources, cooking fuel, consumption of meat, clothing, and the number of meals per day. The recipients of BLT amounted to 29 households from 50 families. From the results of the 50 Alternative Tests, the results of V1 with a value above 0.5 as the alternative were selected as recipients of direct cash assistance.